2011
DOI: 10.1016/j.expneurol.2010.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and neurodegenerative effects of the chronic expression of tumor necrosis factor α in the nigrostriatal dopaminergic circuit of adult mice

Abstract: Neuroprotective and neurodegenerative effects of the chronic expression of tumor necrosis factor alpha in the nigrostriatal dopaminergic circuit of adult mice Chertoff, M.; Di Paolo, N.; Schoeneberg, A.; Depino, A.; Ferrari, C.; Wurst, W.; Pfizenmaier, K.; Eisel, Ulrich; Pitossi, F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 79 publications
1
54
1
Order By: Relevance
“…These results are in agreement with previous findings showing that Sildenafil reduces oxidative stress and inflammatory injuries of the kidney in streptozotocin-diabetic rats [27] and after ischemia and reperfusion [28]. Expression of pro-inflammatory cytokines in injured nerves may have both beneficial and detrimental effects on nerve regeneration or neuropathic pain induction [29,30,31]. In the present manuscript, we demonstrated that BCNR up-regulates the expression of several pro-inflammatory cytokines in the pelvic ganglia; SIL treatment was able to reduce these levels back to that of sham operated animals.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with previous findings showing that Sildenafil reduces oxidative stress and inflammatory injuries of the kidney in streptozotocin-diabetic rats [27] and after ischemia and reperfusion [28]. Expression of pro-inflammatory cytokines in injured nerves may have both beneficial and detrimental effects on nerve regeneration or neuropathic pain induction [29,30,31]. In the present manuscript, we demonstrated that BCNR up-regulates the expression of several pro-inflammatory cytokines in the pelvic ganglia; SIL treatment was able to reduce these levels back to that of sham operated animals.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the proinflammatory cytokine tumor necrosis factor alpha (TNF-α) released by astrocytes triggers the GDNF release from reactive astrocytes in vitro (Kuno et al, 2006). This would not only suggest the activation of an autocrine anti-inflammatory loop but also support the notion that TNF-α acts as a gliotransmitter that may trigger plasticity processes involving GDNF (Fellin, 2009) in addition to the prevention of secondary neuronal degeneration due to inactivity (Chertoff et al, 2011). Moreover, increased levels of GDNF released from astrocytes may directly affect the formation of synapses as well as dendritic and axonal growth as observed in the models of Parkinson's disease (Nakajima et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Chertoff and colleagues have also explored the concept of TNF-α playing dual roles in PD pathophysiology. Young 2-3 month-old mice subjected to 6-OHDA with constitutive, low-level expression of TNF-α are spared in respect to nigrostriatial degeneration, whereas overt neuronal loss and inflammatory responses occurs in mice overexpressing TNF-α, indicating that the level and timing of TNF-α plays a pivotal role in the progression of disease (Chertoff et al 2011). Collectively, these data demonstrate that the development of anti-TNF-α PD therapies requires a highly tuned and selective strategy based upon assiduous examination of the dependence of disease stage, TNF-α levels, cellular context, and individual receptor involvement in multiple models of PD.…”
Section: Parkinson's Diseasementioning
confidence: 99%